Formalnoprawne podstawy działania samorządu terytorialnego jako podmiotu kształtującego warunki rozwoju turystyki w krajach euroregionu Neisse-Nisa-Nysa - Przeorek-Smyka, Renata; Januszewska, Małgorzata (Formal and Legal Basis for the Territorial Government Activities as the Organ Influencing Tourism Development Conditions in the Euroregion Countries, 2005)
The article presents basic, formal and legal solutions for the functioning of territorial government in the three Euroregion countries. It discusses opportunities for utilising the authority at counties' and districts' disposal for defining tourism development directions. It indicates that the range of territorial government organs' influence on tourism industry management is defined, apart form the legal and organisational factors, also by these of economic and social nature.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 26-40